ANALISIS TOTAL FENOLIK, FLAVONOID, DAN AKTIVITAS ANTIOKSIDAN PADA DAUN SERTA BATANG TANAMAN Coleus amboinicus Lour (BANGUN-BANGUN) - I. Yulianto; C. Abdullah; C. Jose (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The objective of this study was to analyze the total phenolics, flavonoids, andantioxidant activity of leaves and stems of C. amboinicus. Two different wateringtreatments (EM5 and FPE) were applied to C. amboinicus during cultivation. Theresults showed that leaves of C. amboinicus treated with FPE had the highest totalphenolic and flavonoid content than other samples. The total phenolic content was2.09 mg Gallic Acid Equivalent (GAE)/g of dry weight (DW) and the total flavonoidcontent was 6.218 mg Catechin Equivalent (CTE)/g of DW respectively. The leavestreated with FPE also had the highest antioxidant activity by FRAP test (0.058 mmolFe +2 /g DW). The highest antioxidant activity by DPPH test was found in the leavestreated with EM5 (1.42 mg Ascorbic Acid Equivalent (AAE)/g DW). From this study itcan be concluded that leaves of C. amboinicus was the best source of antioxidant. FPEwatering treatment gave a better influence on total phenolic, flavonoid, and antioxidantactivity of C. amboinicus than EM5.